2015
DOI: 10.1080/00220388.2015.1036036
|View full text |Cite
|
Sign up to set email alerts
|

Can Integrated Agriculture-Nutrition Programmes Change Gender Norms on Land and Asset Ownership? Evidence from Burkina Faso

Abstract: This article uses a mixed-methods approach to analyse the impact of an integrated agriculture and nutrition programme in Burkina Faso on women’s and men’s assets, and norms regarding ownership, use and control of assets. We use a cluster-randomised controlled trial to determine whether productive asset transfers and increased income-generating opportunities for women increase women’s assets over time. Qualitative work on gender norms finds that although men still own and control most assets, women have greater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 28 publications
0
24
0
Order By: Relevance
“…By increasing access to program inputs, control over resources, and maternal knowledge of and ability to implement optimal agriculture, nutrition, and health practices, the program was expected to improve women's bargaining power, particularly over the resources needed for maternal and child health and nutrition. A cluster‐randomized controlled trial showed that the program reduced gender asset inequality: women's value of agricultural assets in intervention villages increased, whereas men's decreased (van den Bold et al., ). Although the project had no impact on the area of land cultivated by either men or women, qualitative work indicates that gender norms became more favorable toward women's landownership in treatment as compared with control areas.…”
Section: Evidence From Impact Evaluationsmentioning
confidence: 99%
“…By increasing access to program inputs, control over resources, and maternal knowledge of and ability to implement optimal agriculture, nutrition, and health practices, the program was expected to improve women's bargaining power, particularly over the resources needed for maternal and child health and nutrition. A cluster‐randomized controlled trial showed that the program reduced gender asset inequality: women's value of agricultural assets in intervention villages increased, whereas men's decreased (van den Bold et al., ). Although the project had no impact on the area of land cultivated by either men or women, qualitative work indicates that gender norms became more favorable toward women's landownership in treatment as compared with control areas.…”
Section: Evidence From Impact Evaluationsmentioning
confidence: 99%
“…Programs on homestead food production typically combine support for agricultural production with nutrition BCC. The enhanced-homestead food production (EHFP) program in Burkina Faso, implemented by Helen Keller International (HKI), provided inputs and training to women beneficiaries of the program and negotiated with the community for land on which women could establish a village model farm (van den Bold et al, 2015). The program had an explicit goal of improving children's nutrition outcomes, targeted to households with women and children in the first 1000 days, and integrated agriculture production activities with a strong nutrition and health BCC strategy (Olney et al, 2015).…”
Section: Resource Transfers + Nutrition Bcc Targeted To Womenmentioning
confidence: 99%
“…A randomized evaluation of similar programs in six countries showed "that 'big push' which includes large asset transfer does help overcome poverty traps and has positive economic outcomes (on per-capita consumption, household assets and food security) that are maintained a year after the program ends" (Buvinic and O'Donnell, 2016). An asset-transfer program in Burkina Faso indicated that women's control over and ownership of assets improved social perceptions about asset ownership, which demonstrates that social norms can be shifted (van den Bold et al, 2013). Programs that give women control of farm land have been classified as proven to increase the productivity and economic security of women farmers (Buvinic and O'Donnell, 2016).…”
Section: Endowments 221 Assetsmentioning
confidence: 99%